2020
DOI: 10.1088/2053-1591/ab6e7e
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Comparative study of hot corrosion behavior of thermal sprayed alumina and titanium oxide reinforced alumina coatings on boiler steel

Abstract: The current work evaluates the effect of hot corrosion on ASTM-SA213-T-22 Steel with a coating of 100Al 2 O 3 and 20TiO 2 -Al 2 O 3 at 900°C in the molten salt environment of (Na 2 SO 4 -60% V 2 O 5 ). The coatings were sprayed by plasma spray technique. The bare and coated samples were placed inside the muffle furnace at 900°C for 50 cycles. Each cycle consisted of heating for 1 h and 20 min of cooling at ambient temperature. The kinetics of hot corrosion was analyzed by measuring mass gain after each cycle. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 43 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…The rapid development of the industry has led to increasingly higher requirements for the performance and service life of various mechanical parts [1][2][3]. Wear and corrosion are the prime reasons for material failure during use, which seriously affect the performance quality and service life of mechanical products [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of the industry has led to increasingly higher requirements for the performance and service life of various mechanical parts [1][2][3]. Wear and corrosion are the prime reasons for material failure during use, which seriously affect the performance quality and service life of mechanical products [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the major problems in thermal power plant are corrosion, oxidation and erosion. However, various authors [16][17][18][19][20][21][22][23][24][25][26][27][28][29] have used various types of coatings to combat high temperature oxidation, erosion corrosion. But, the use of AL in power plant can play a significant role.…”
Section: E Al In Power Stationmentioning
confidence: 99%
“…Evaluation of hot corrosion on ASTM-SA213-T-22 Steel with coatings of 100Al 2 O 3 and 20TiO 2 -Al 2 O 3 by plasma spray at 900 °C was done in a molten salt environment of (Na 2 SO 4 -60% V 2 O 5 ). The results demonstrated that uncoated steel was severely corroded and gained more mass, 20TiO 2 -Al 2 O 3 coating provides temperature resistance with an increased lifetime [8]. Using high process temperatures and pyrolysis, an ash and sludge environment was induced for corrosion study on a (CMT)-clad Inconel 625. longterm corrosion experiments were conducted at 650 °C for 1000 h. The biomass ashes created deep corrosion layers (about 5-15 μm), whereas the sewage sludge ash caused shallow corrosion layers (approximately 1-5 μm) [9].…”
Section: Introductionmentioning
confidence: 99%